Effect of pH on Adsorption and Photocatalytic Degradation Efficiency of Different Catalysts on Removal of Methylene Blue - Alkaim1, A.F.; Aljeboree1, A.M.; Alrazaq1, N.A.; Baqir2, S.J.; Hussein2, F.H.; Lilo2, A.J. (Asian Journal of Chemistry, 2014)
The present study investigates the efficiency of adsorption and photodegradation catalyzed by TiO2, ZnO, CdS and Co3O4 on the removal of methylene blue dye, in different pH values (4, 6, 9 and 11). The photocatalytic degradation of methylene blue dye in aqueous catalysts TiO2, ZnO, CdS and Co3O4 suspension follows apparent after 0.5 h of photodegradation a first-order kinetics. The photodegradation efficiency of methylene blue was fast in the present condition (pH 11, pH 6, pH 6 and pH 4) and slower in (pH 4, pH 11, pH 11 and pH 11) of ZnO, TiO2, CdS and Co3O4, respectively. The highest adsorption capacity as follow: TiO2 > ZnO » CdS » Co3O4, while the photocatalytic activity: ZnO > TiO2 > CdS > Co3O4.